Acute gastrointestinal bleeding – a new approach to clinical and endoscopic management. Issue 5 (May 2015) - Rey, Johannes W.; Fischbach, Andreas; Teubner, Daniel; Dieroff, Marc; Heuberger, Dominik; Nguyen-Tat, Marc; Manner, Hendrik; Kiesslich, Ralf; Hoffman, Arthur
Abstract : Overt or occult gastrointestinal bleeding is a frequently observed condition in routine gastroenterological practice. Occult gastrointestinal bleeding is usually a purely incidental finding, based on the discovery of iron deficiency anemia in the laboratory or blood in stool (a positive Hemoccult test). However, overt bleeding accompanied by the clinical features of tarry stool, hematemesis, or hematochezia may be a life-threatening condition, calling for immediate emergency management. In contrast to traumatology, algorithms of emergency and intensive medicine are not sufficiently validated yet for acute life-threatening bleeding. The purpose of this review was to present all established and new endoscopic hemostasis techniques and to evaluate their efficacy, as well as to provide the treating endoscopist with practical advice on how he/she could incorporate these procedures into acute medical management. The recommendations are based on inspection of the study results in the recent published literature, as well as emergency medicine algorithms in traumatology.